Multi-Peak Solutions for Coupled Nonlinear Schrodinger Systems in Low Dimensions - Zheng, Maoding; Zhang, Binlin; Radulescu, Vicentiu (Springer Nature, 2023)
In this paper, we construct the solutions to the nonlinear Schrodinger system. We construct the solution for attractive and repulsive cases. When $x_0$ is a local maximum point of the potentials P and Q and $P(x_0) = Q(x_0)$, we construct k spikes concentrating near the local maximum point $x_0$. When x_0$ is a local maximum point of P and $x^{\ bar}_ 0$ is a local maximum point of Q, we construct k spikes of $ u $ concentrating at the local maximum point $ x_0$ and m spikes of v concentrating at the local maximum point $x^{\ bar}_ 0$ when $x_0 \ not = $x^{\ bar}_ 0$ This paper extends the main results established by Peng and Wang (Arch Ration Mech Anal 208:305-339, 2013) and Peng and Pi (Discrete Contin Dyn Syst 36:2205-2227, 2016), where the authors considered the case N = 3, p = 3.

In this paper, we construct the solutions to the nonlinear Schrodinger system. We construct the solution for attractive and repulsive cases. When $x_0$ is a local maximum point of the potentials P and Q and $P(x_0) = Q(x_0)$, we construct k spikes concentrating near the local maximum point $x_0$. When x_0$ is a local maximum point of P and $x^{\ bar}_ 0$ is a local maximum point of Q, we construct k spikes of $ u $ concentrating at the local maximum point $ x_0$ and m spikes of v concentrating at the local maximum point $x^{\ bar}_ 0$ when $x_0 \ not = $x^{\ bar}_ 0$ This paper extends the main results established by Peng and Wang (Arch Ration Mech Anal 208:305-339, 2013) and Peng and Pi (Discrete Contin Dyn Syst 36:2205-2227, 2016), where the authors considered the case N = 3, p = 3.
Multi-Peak Solutions for Coupled Nonlinear Schrodinger Systems in Low Dimensions
Keywords: Nonlinear Schrodinger system; Lyapunov-Schmidt reduction; Singularity; Perturbation; Nonlinear Schrodinger system; Lyapunov-Schmidt reduction; Singularity; Perturbation